If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8r + 10 = 4r + 3 Reorder the terms: 10 + 8r = 4r + 3 Reorder the terms: 10 + 8r = 3 + 4r Solving 10 + 8r = 3 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 10 + 8r + -4r = 3 + 4r + -4r Combine like terms: 8r + -4r = 4r 10 + 4r = 3 + 4r + -4r Combine like terms: 4r + -4r = 0 10 + 4r = 3 + 0 10 + 4r = 3 Add '-10' to each side of the equation. 10 + -10 + 4r = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 4r = 3 + -10 4r = 3 + -10 Combine like terms: 3 + -10 = -7 4r = -7 Divide each side by '4'. r = -1.75 Simplifying r = -1.75
| 49x^4-14x^3-28x^2=0 | | f(x)=x^4+2x^3-2x^2+1 | | 3k^3+22k^2+7k=0 | | y=(3x+9)(x-5) | | 7x-6+3x-5+4x-5=180 | | 3e^5x+3=12 | | 4/7=68/m | | 4z^2-12z+9= | | 121-k^2=0 | | -7+2.5=19-4 | | 3x*10=140 | | 4x^3-16x^2-24x=0 | | 5x^3-18x^2-9x=0 | | 6x-7=-r | | 4c*7e= | | 3x*10=1p | | 5x^3-18x^2-18x=0 | | -28+47x=270 | | 9+2y=4y+5 | | 7a^3+53a^2+28a=0 | | 5x-17=2x+5 | | 7a^3+53a^2+28=0 | | 7a^3+53a+28=0 | | y(10-(10-y))=(10-y)(21-2y) | | (6n^2+6n-3)(6n^2+5n-5)= | | 2(x*x)-x-6=0 | | cos(3.14x)=4x^2-1 | | x-3=x+7 | | 6x+21=15 | | 10x-35x+4=18 | | B=1-a^2 | | 3x^2y*4xy^3= |